2022
DOI: 10.3390/su14094914
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Uptake of CuO Nanoparticles: Evaluation of an Emerging Nanofertilizer on Wheat (Triticum aestivum L.) Plant

Abstract: Wet chemistry was used to produce copper oxide nanoparticles (CuO NPs). The results indicated that most nanoparticles were bacillus-shaped and relatively uniform in size (less than 30 nm). The effect of synthesized CuO NPs on wheat (Triticum aestivum L.) germination and growth parameters was studied and compared to bulk Cu. The results showed that no significant difference was obtained in germination rate among all treatments. Bulk Cu additions significantly affect the mean germination rate and mean germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 90 publications
2
2
0
Order By: Relevance
“…To our knowledge, there have been no prior reports on seed germination inhibition due to application of HgO-NPs, while inhibitory impacts of other nano-sized heavy metals on seed germination of several plants have been studied. For example, declines of germination indicators were recorded in wheat treated with CuO NPs (Ibrahim et al, 2022), rice treated with Y2O3-NPs (Zhao et al, 2021) and maize treated with PbS-NPs (Ullah et al, 2020), Al2O3 and TiO2-NPS (Karunakaran et al, 2016). All these studies have consistently shown that the toxicity of the applied NPs increases in tandem with the dose, which aligns with our data.…”
Section: Hgo-nps Application Delayed Germination Of Maize Seedssupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, there have been no prior reports on seed germination inhibition due to application of HgO-NPs, while inhibitory impacts of other nano-sized heavy metals on seed germination of several plants have been studied. For example, declines of germination indicators were recorded in wheat treated with CuO NPs (Ibrahim et al, 2022), rice treated with Y2O3-NPs (Zhao et al, 2021) and maize treated with PbS-NPs (Ullah et al, 2020), Al2O3 and TiO2-NPS (Karunakaran et al, 2016). All these studies have consistently shown that the toxicity of the applied NPs increases in tandem with the dose, which aligns with our data.…”
Section: Hgo-nps Application Delayed Germination Of Maize Seedssupporting
confidence: 90%
“…Once accumulated in soil, toxic agents such as heavy metal nanoparticles (HM-NPs) inhibit seeds germination and development of early seedlings in several plants (Asadi-Kavan et al, 2020;Seddighinia et al, 2020). In this regard, retardation of germination and growth of young seedlings due to nano-sized heavy metals, such as PbS-NPs (Ullah et al, 2020), CuO-NPs (Ibrahim et al, 2022), Y2O3-NPs (Zhao et al, 2021) and ZnO NPs (Yang et al, 2023), have been studied in maize, wheat, rice and Arabidopsis thaliana, respectively. These authors ascribed the delaying of seed germination and deterioration of seedling growth to: (a) deactivation of seed' amylase and protease via formation of S-Metal-S bridges instead of -SH group in the enzyme' proteins (b) blocking of aquaporins delay the rupture of seed coat and emergence of radical (c) restraining water imbibition and uptake due to metal-induced ionic toxicity (d) generation of free radicals and cellular oxidative damage, (e) decreasing internodal length and plant height and (f) distortion of root structures and disruption of water uptake.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with those results obtained from exposed Mung beans [29] and maize seeds [56], TiO 2 NPs were able to penetrate pomegranate seeds, as confirmed through TEM, XRF, and ICP-OES, which is the first direct evidence of TiO 2 NP uptake in pomegranate seed tissues. Such evidence of TiO 2 internalization by plant tissues is also in accordance with a variety of other metal-based nanoparticles, including Fe 3 O 4 , Au, and Cu nanoparticles [57][58][59].…”
Section: Discussionsupporting
confidence: 75%
“…This appears further encouraging in light of the similar repots highlighting soil organic carbon's role in nutrient mobilisation and environmental sustainability 16 , 31 , 33 . However, amid increasing concerns over the bio and environmental compatibility of the poorly defined nanomaterials and lack of enough information over their mechanism and efficiency, this needs vigorous investigation 37 , 38 .
Figure 9 A schematic diagram showing the whole process from the synthesis of the ZnO NPs to its application; The interaction between negatively charged soil colloidal carbon surface with positively charged ZnO NPs (sheet-like structure); nano surfaces along with other mineral nutrients interactions in soil solution for nutrient uptake efficiency has also been shown.
…”
Section: Resultsmentioning
confidence: 99%